Learning Management Based on Active Deep Learner Experience (ADLX) in Developing Teacher Innovation and Competence (Case Study at SMPIT Al Uswah Surabaya) - Ismiatiningsih Ismiatiningsih*; Erny Roesminingsih; Karwanto Karwanto (Riwayat: Educational Journal of History and Humanities, 2023)
SMPIT Al Uswah is one of the SMPITs under the auspices of the Integrated Islamic School Network which implements a learning system that prioritizes memorizing the Koran and also leadership, according to the school's motto, namely "Tahfidz and Leadership". By combining the integrated learning concept between the government curriculum and the Integrated Islamic School Network curriculum, cooperative learning, and Project Learning, teaching staff are expected to be able to innovate in developing media and learning strategies so that students do not feel bored. The Active-Deep Learner eXperience (ADLX) learning design combined with the Study, Exploration, Formulate, Present, Apply, Worldly, and Ukhrowi (TERPADU) learning concept is carried out as one of the learning innovations. The learning planning management prepared in the ADLX learning design uses a constructivist theory approach where learning planning places more emphasis on the learning experience of students. To meet these needs, the school strives to encourage all teachers at SMPIT Al Uswah Surabaya to take part in the ADLX training program so that teacher competency and innovation can be developed, and teachers gain extraordinary learning experiences that can be applied at school. This experience includes experience in planning learning, applying ADLX learning designs in schools, preparing assessments of ADLX learning activities, making evaluation plans for the implementation of ADLX learning, and being able to create innovative learning methods and learning media according to the needs and character of students at school.